Transfer Teknologi Sero Jaring Berbasis Partisipasi untuk Peningkatan Hasil Tangkapan Bibit Ikan Budidaya dan Domestikasi Nelayan Tradisional Desa Wawobungi, Konawe - Abdul Muis Balubi; Syamsul Kamri; Ruslaini; Abdul Hamid; Bobby Afyudi; La Ode Muhammad Aslan; La Ode Aslin; Indrayani; Hasnia Arami; Asis Bujang; Arman Pariakan; Muhammad Manshur Taufiq (Universitas Mataram, 2026)
This community service program aimed to enhance the capacity of traditional fishers in Wawobungi Village, Lalonggasumeeto Subdistrict, Konawe Regency, to construct, install, and operate sero jaring, a passive tidal-based fishing gear used to provide fish seed for aquaculture and domestication. The activity was conducted from April to July 2023 through a participatory technology transfer approach based on local assets. The program included site surveys, mapping of fish migration routes, designing a five-part sero structure, construction training, gear installation, and monitoring of catch composition. The results showed that sero jaring was able to capture multispecies commodities, including trevally, rabbitfish, grouper, Napoleon wrasse, squid, cuttlefish, sea catfish, scad, flying fish, and halfbeak. The highest catch frequencies were found in squid, trevally, and streaked spinefoot, indicating the potential of sero as a source of natural fish seed and coastal food resources. This activity demonstrated the strengthening of an assistance model that integrates fish migration route mapping, appropriate technology design, participatory monitoring, and downstream development toward floating net cages and integrated aquaculture. This program contributes to strengthening fishers’ economic capacity, reducing operational costs, improving ecological knowledge, and formulating a coastal fisheries empowerment model that can be contextually replicated. Keywords: Setnet; traditional fishers; small-scale fisheries; aquaculture fish seed; domestication; Wawobungi.